Transcriptomics Profiling Identifies Cisplatin-Inducible Death Receptor 5 Antisense Long Non-coding RNA as a Modulator of Proliferation and Metastasis in HeLa Cells - Gurer, Dilek Cansu; Erdogan, İpek; Ahmadov, Ulvi; Basol, Merve; Sweef, Osama; Cakan-Akdogan, Gulcin; Akgül, Bünyamin (Frontiers in Cell and Developmental Biology, 2021)
Cisplatin is a well-known cancer chemotherapeutic agent but how extensively long noncoding RNA (lncRNA) expression is modulated by cisplatin is unknown. It is imperative to employ a comprehensive approach to obtain a better account of cisplatin-mediated changes in the expression of lncRNAs. In this study, we used a transcriptomics approach to profile lncRNAs in cisplatin-treated HeLa cells, which resulted in identification of 10214 differentially-expressed lncRNAs, of which 2500 were antisense lncRNAs. For functional analyses, we knocked down one of the cisplatin inducible lncRNAs, death receptor 5 antisense lncRNA (DR5-AS), which resulted in a morphological change in HeLa cell shape without inducing any cell death. A second round of transcriptomics-based profiling revealed differential expression of genes associated with immune system, motility and cell cycle in DR5-AS-silenced HeLa cells. Cellular analyses showed that DR5-AS reduced cell proliferation and caused a cell cycle arrest at S and G2/M phases. Moreover, DR5-AS knockdown reduced the invasive capacity of HeLa cells in zebrafish xenograft model. These results suggest that cisplatin-mediated pleiotropic effects, such as reduction in cell proliferation, metastasis and cell cycle arrest, may be mediated by long noncoding RNAs.